Answer:
Step-by-step explanation:Simplifying
3x + 8 = 2x + -21
Reorder the terms:
8 + 3x = 2x + -21
Reorder the terms:
8 + 3x = -21 + 2x
Solving
8 + 3x = -21 + 2x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-2x' to each side of the equation.
8 + 3x + -2x = -21 + 2x + -2x
Combine like terms: 3x + -2x = 1x
8 + 1x = -21 + 2x + -2x
Combine like terms: 2x + -2x = 0
8 + 1x = -21 + 0
8 + 1x = -21
Add '-8' to each side of the equation.
8 + -8 + 1x = -21 + -8
Combine like terms: 8 + -8 = 0
0 + 1x = -21 + -8
1x = -21 + -8
Combine like terms: -21 + -8 = -29
1x = -29
Divide each side by '1'.
x = -29
Simplifying
x = -29